A Porcine Congenital Single-Sided Deafness Model, Its Population Statistics and Degenerative Changes - Ren, Wei; Xu, Cong; Zheng, Fan-jun; Lin, Ting-ting; Jin, Peng; Zhang, Yue; Guo, Wei-wei; Liu, Chuan-hong; Zhou, Xiao-yang; Wang, Lu-lu; Wang, Yong; Zhao, Hui; et al. (Frontiers in Cell and Developmental Biology, 2021)
Objective To describe and study the population statistics, hearing phenotype and pathological changes of the porcine congenital single-sided deafness (CSSD) pedigree. Methods Click-ABR, full-frequency ABR and DPOAE were used to assess the hearing phenotype of the strain. Tympanogram was used to assess the middle ear function since birth. Celloidin embedding-hematoxylin-eosin Stain (CE-HE) and scanning electron microscope (SEM) were used to study the pathological changes of cochlear micro-structures. Chi-square analysis was used to analyze the relation between hearing loss and other phenotypes. Results In our strain, the mating mood of CSSD with CSSD was most efficient in producing targeted CSSD phenotype (47.62%) and the prevalence of CSSD reached 46.67% till the fifth generation with 42.22% were bilateral hearing loss (BHL) and 9.00% were normal hearing (NH) individuals. Hearing loss was proved to have no relation with coat color(P=0.0841>0.05) and gender(P=0.4621>0.05) by chi-square analysis. The deaf side of CSSD offspring in 5th generation had no relation with that of their maternal parent (P=0.2387>0.05) and the paternal pig was the same R-CSSD individual. All individuals in this strain exhibited congenital severe to profound sensorineural hearing loss with no malformation and dysfunction of middle ear. The good hearing ear of CSSD stayed stable over age. The deaf side of CSSD and BHL presented cochlear and saccular degeneration, hair cell exhibited malformation since birth and degenerated from apex to base turn through time. The pathology in BHL cochlea progressed more rapid than CSSD and till P30, hair cell had been totally gone. The stria vascularis was normal since birth and degenerated through time and finally exhibited disorganization of three layers of cells Conclusion Our inbred porcine strain exhibited high and stable prevalence of CSSD individuals which presented congenital single-sided hearing loss and highly resembled human non-syndromic CSSD disease. This porcine model could be used to further explore the etiology of CSSD and serve as an ideal tool for the studies of the effects of single-side hearing deprivation on neural, cognitive and behavioral developments.